2004
DOI: 10.1038/sj.mp.4001502
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of serotonin-related genes in antidepressant response

Abstract: In this study, we sought out to test the hypothesis that genetic factors may influence antidepressant response to fluoxetine. The investigation focused on seven candidate genes in the serotonergic pathway involved in the synthesis, transport, recognition, and degradation of serotonin. Our clinical sample consisted of 96 subjects with unipolar major depression treated with fluoxetine with response variables assessed after a 12-week trial. Patient data were also collected to investigate the pattern of drug respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
157
4
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(172 citation statements)
references
References 59 publications
(66 reference statements)
9
157
4
2
Order By: Relevance
“…39,41,42,58 Clinical association studies have further examined the relationship between SERTLPR alleles and psychiatric disorders and anxiety-related personality traits, [59][60][61][62][63][64][65][66] suicide, 67,68 alcoholism, 69,70 response to antidepressants [71][72][73] and brain function as revealed by MRI scans. [74][75][76][77] Although many studies have reported correlations between SERTLPR alleles and SERT expression levels or clinical phenotype, almost an equal number of studies have not.…”
Section: Discussionmentioning
confidence: 99%
“…39,41,42,58 Clinical association studies have further examined the relationship between SERTLPR alleles and psychiatric disorders and anxiety-related personality traits, [59][60][61][62][63][64][65][66] suicide, 67,68 alcoholism, 69,70 response to antidepressants [71][72][73] and brain function as revealed by MRI scans. [74][75][76][77] Although many studies have reported correlations between SERTLPR alleles and SERT expression levels or clinical phenotype, almost an equal number of studies have not.…”
Section: Discussionmentioning
confidence: 99%
“…Although not covering the locus systematically, several previous studies have provided suggestive evidence for an involvement of other HTR2A variants in antidepressant outcome (Minov et al, 2001;Cusin et al, 2002;Peters et al, 2004;Choi et al, 2005;Hong et al, 2006;Kato et al, 2006;McMahon et al, 2006;Paddock et al, 2007;Perlis et al, 2009). Post-mortem (McKeith et al, 1987Lopez-Figueroa et al, 2004) and positron emission tomography (PET) (Yates et al, 1990;Yatham et al, 2000;Mintun et al, 2004) studies have reported both increased and decreased HTR2A receptor number and binding in different brain regions of depressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 A wider list of polymorphism should be investigated to achieve a better resolution given that other control regions may be present for the 5-HTT expression, not to mention possible enhancers or silencers located in other regions far from the gene locus. In fact, Hamilton et al 28,41 reported a significant association of a functional SNP (rs25531) 42,43 located just upstream of the 5-HTTLPR with antidepressant response to fluoxetine treatment and in linkage disequilibrium (LD) with 5-HTTLPR. In the presence of the g allele of this SNP, the l allele of 5-HTTLPR seems to be associated with nonresponse, while this is the case for the s allele in presence of the a allele of the SNP.…”
Section: -Httlpr and Ssri Meta-analysismentioning
confidence: 99%